2000
DOI: 10.1007/s004310050046
|View full text |Cite
|
Sign up to set email alerts
|

DNase use in the daily care of cystic fibrosis: who benefits from it and to what extent? Results of a cohort study of 199 patients in 13 centres

Abstract: The benefits of DNase use in daily practice are limited but apparently can be maintained in the medium term in some patients. A large inter-individual variability in response to DNase treatment has been documented and the benefits are doubtful in around 50% of patients. This observation points to the need to set up a withdrawal trial in these patients, using as an eligibility criterion the early response observed during the first 3 months of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…[18][19][20] Our data show that sputum obtained from such clinical non-responders could also not be degraded in vitro with rhDNase-I, while sputum from clinical responders was extensively degraded by rhDNase-I. More importantly, biochemical analysis revealed that clinical responders produced sputum that contained significantly higher concentrations of potassium (and especially magnesium) than sputum from clinical non-responders.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…[18][19][20] Our data show that sputum obtained from such clinical non-responders could also not be degraded in vitro with rhDNase-I, while sputum from clinical responders was extensively degraded by rhDNase-I. More importantly, biochemical analysis revealed that clinical responders produced sputum that contained significantly higher concentrations of potassium (and especially magnesium) than sputum from clinical non-responders.…”
Section: Discussionmentioning
confidence: 71%
“…[15][16][17] Indeed, different studies have shown a wide variation in the clinical response to rhDNase-I with about 30% of patients-the so-called non-responders-not benefiting from it. [18][19][20] The reason for the failure of rhDNase-I in these patients is not understood. This study was therefore undertaken to elucidate the reason for the failure of rhDNase-I in certain CF patients and to evaluate strategies to overcome this.…”
mentioning
confidence: 99%
“…However, dornase alfa does not improve lung function in all patients (14,16), and there is a need to develop novel mucolytic therapies with the goal of improving lung function and delivery of inhaled drugs, including gene therapy vectors, to the bronchial epithelium (30). Alternative approaches include the use of inhaled osmotic agents such as hypertonic saline and mannitol (17) as mucomodulators that, by setting up osmotic gradients, improve periciliary fluid hydration and mucus clearance.…”
mentioning
confidence: 97%
“…Sixty-five out of 184 (35%) patients experienced 106 episodes of airway reactivity in response to nebulized rhDNase [45]. However, most studies did not demonstrate significantly more BHR, dyspnea, cough, wheeze and/or increased pulmonary obstruction in CF patients compared to controls (Supplementary Tables 1) [42,[46][47][48][49][50][51][52][53][54].…”
Section: Rhdnasementioning
confidence: 99%